Stress Cardiomyopathy Managed with Extracorporeal Support after Self-Injection of Epinephrine - Bourenne Jeremy; Fresco Raphaëlle; Kerbaul François; Michelet Pierre; Gainnier Marc (Case Reports in Critical Care)
A 28-year-old man was admitted to the ICU for self-injection of Epinephrine. This injection resulted in the rapid development of a catecholamine-induced cardiomyopathy (inverted Takotsubo) with a severe cardiogenic shock. The importance of ventricular dysfunction required the implementation of a temporary arteriovenous circulatory support until the recovery of myocardial stunning. This case allows redefining the role of circulatory assistance during cardiotropic agents intoxication.